The Design of Educational Programs in System Dynamics at Worcester Polytechnic Institute (WPI) - Oleg V. Pavlov; James K. Doyle; Khalid Saeed; James M. Lyneis; Michael J. Radzicki (Systems, 2014)
Educational programs leading to degrees in system dynamics are rare and thus of critical importance to the future of the field of system dynamics. However, to a large extent such programs have not yet been made transparent to the system dynamics community as a whole. The present article describes the design and rationale for undergraduate and graduate programs at Worcester Polytechnic Institute (WPI). The goal of the article is to invite feedback from the system dynamics community about our specific programs as well as to facilitate wider discussion about the appropriate content, design, and pedagogy of degree programs and courses in system dynamics.